Readiness of Students in Flexible Learning Modality: A Convergent Parallel Mixed-Methods Study - Rodrigo Jr Licayan; Herrera, Angelli B; Bersano, Michelle S; Idul, Rocris Glenn R (International Journal of Asian Education, 2021)
This convergent-parallel mixed-methods study was conducted to examine students' readiness on flexible learning modality established in the local context based on Commission on Higher Education Memorandum Order No. 04 series of 2020 or the "Guidelines on the Implementation "Flexible Learning in the Philippines." A sample of  408 students participated in the study. The self-determination theory model and contextual approach to e-learning delivery (learning flexibility, online learning, study management, technology, modular learning, and online interaction) were used as theoretical underpinnings. Data collected using electronic surveys and information from semi-structured interviews were analyzed. The application of a descriptive survey confirms the low level of readiness among students. When compared across the population, the results provided no significant difference in the level of readiness among students when grouped according to sex and provided significant difference according to year level and Course. Interpreting the results together with qualitative analysis parallels the notion of difficulties among students in all dimensions of flexible learning. This research places the thrust of improving curriculum delivery by addressing flexible learning policies in the local context.